Konversi Sampah Plastik Menjadi Bahan Bakar Alternatif: Metode Systematic Literatur Review - Indriyati, Nor; Rahmah, Nur; Jumriani, Jumriani (JURNAL BIOSHELL, 2024)
Trends in society show that people are depending on the use of plastic materials, due to the nature of plastic which is anti-rust, cheap, practical and lightweight. This trend causes the plastic waste in the environment out of the control. It takes a long time for plastic waste to be degraded by nature, and will cause environmental pollution if it is too late to deal with it. On the other hand, people's need for fuel increasingly, but the availability of the fuel on the nature are rared. Therefore, the effort in changging the plastic waste into fuel are important so that the problem of environmental pollution as well as the scarcity of fossil fuels can be overcome at once. Literature review is the method chosen in this study, where this method selects journals related to the conversion of plastic waste so that it can be used as fuel. The conclusion is the plastic waste can be converted into fuel through several methods, including cracking and pyrolysis, tools and materials needed can be obtained from the surrounding environment so that production costs can be reduced.